ERROR OF CONTROL OF ELECTRICAL INSULATION STRUCTURES BY DIELECTRIC ABSORPTION PARAMETERS ACCORDING TO THE CONCEPT OF UNCERTAINTY OF MEASUREMENTS - G. V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2020)
Introduction. Measurements on alternating current of dielectric absorption parameters – capacitance and dielectric loss tangent tgδ allow us to evaluate the quality of insulation of cables, electrical machines, transformers, etc., both at the technological stage of manufacture and in operation. An increase in the reliability of the measurement result of the parameters is provided by a decrease in the measurement error due to the improvement of measuring instruments and measurement methods and an increase in the number of measurements Purpose. The estimation of the error of control of electrical insulation structures by dielectric absorption parameters in accordance with the concept of measurement uncertainty. Methodology. The error of measurements of the capacitance and the tangent of the dielectric loss angle is estimated using the example of a twisted unshielded pair of category 5e. A statistical analysis of the results of multiple measurements of the capacitance and the tangent of the dielectric loss angle of an unshielded cable is carried out. The linear regression equations for the measured values of the dielectric absorption parameters of the number of measurements are obtained. Practical value. Ensuring unity in the methods for estimating the error of measurement results, both when using the traditional concept of «measurement result error» and when introducing the concept of «measurement result uncertainty» into practice, it will allow to unambiguously interpret and correctly compare the results of measurements of the capacitance and tangent of the dielectric loss angle of electrical insulation structures.